Double primary biliary malignancy: synchronous gallbladder carcinoma and extrahepatic cholangiocarcinoma in a Whipple specimen—a case report and literature review - Agarwal, Arti; Gupta, Manish Kumar; Sarda, Hitesh; Aggarwal, Roopak; Singh, Ekta (Annals of Pancreatic Cancer, 2026)
Background: Synchronous primary malignancies of the gallbladder and extrahepatic bile duct are exceptionally rare, with fewer than 20 histologically confirmed cases reported worldwide. This rarity creates significant diagnostic pitfalls, as such dual primaries are frequently misclassified as metastatic disease, with profound implications for management and prognosis.Case Description: A 73-year-old female presented with painless obstructive jaundice and weight loss. Radiological evaluation revealed two geographically distinct lesions involving the gallbladder fundus and the distal common bile duct. After multidisciplinary discussion and preoperative optimization including endoscopic biliary drainage for severe hyperbilirubinemia (18.2 mg/dL), she underwent a Whipple procedure with wedge liver resection. Histopathology confirmed two separate moderately differentiated adenocarcinomas: gallbladder carcinoma (pT2bN1, Stage IIIB) and distal common bile duct carcinoma (pT3N2, Stage IIIA). Immunohistochemistry was pivotal: both tumors were CK7 and MUC1 positive; crucially, MOC31 was negative in the gallbladder tumor but strongly positive in the bile duct tumor, confirming distinct clonal origins and fulfilling Warren-Gates criteria for synchronous primaries.Conclusions: This case underscores the importance of meticulous radiological-pathological correlation and immunohistochemistry in accurately diagnosing synchronous biliary primaries. Field cancerization is a plausible etiological mechanism in cases without anomalous pancreaticobiliary duct union. Complete surgical resection guided by a multidisciplinary approach offers potential for cure.